Acquisition of Fc-afucosylation of PfEMP1-specific IgG is age-dependent and associated with clinical protection against malaria - Mary Lopez-Perez; Zakaria Seidu; Mads Delbo Larsen; Wenjun Wang; Jan Nouta; Manfred Wuhrer; Gestur Vidarsson; Michael F. Ofori; Lars Hviid (Nature Communications)
Abstract Protective immunity to malaria depends on acquisition of parasite-specific antibodies, with Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) being one of the most important target antigens. The effector functions of PfEMP1-specific IgG include inhibition of infected erythrocyte (IE) sequestration and opsonization of IEs for cell-mediated destruction. IgG glycosylation modulates antibody functionality, with increased affinity to FcγRIIIa for IgG lacking fucose in the Fc region (Fc-afucosylation). We report here that selective Fc-afucosylation of PfEMP1-specific IgG1 increases with age in P. falciparum-exposed children and is associated with reduced risk of anemia, independent of the IgG levels. A similar association was found for children having PfEMP1-specific IgG1 inducing multiple effector functions against IEs, particularly those associated with antibody-dependent cellular cytotoxicity (ADCC) by NK cells. Our findings provide new insights regarding protective immunity to P. falciparum malaria and highlight the importance of cell-mediated destruction of IgG-opsonized IEs.